Pemeriksaan Serta Pemeliharaan Pada Rel 1 Bay Saketi - Dede Eful Ginanjar; Irwanto Irwanto (Politeknik Kampar, 2025)
This research aims to find out about the main substation, good rails (busbars) in the substation system, and inspection and maintenance of the 1 bay Saketi rail. The place and time for industrial practice is carried out at PT. PLN Persero ULTG Rangkasbitung Jl. Rawasari, West Rangkasbitung, District. Rangkasbitung District. Lebak, Banten Province. The implementation time is from 28 November to 28 December 2022 with 5 working days. In this research it was found that rails (busbars) require protection if used in open areas. This avoids a short circuit if a metal object falls on the positive or negative busbar. At one substation there are several types of busbar configurations, including: (1) single bus; (2) double bus-double breaker; (3) main and transfer buses; (4) double bus-single breaker; (5) ring bus; and (6) break and a half.